137Cs ocean distribution and fate at East Mediterranean Sea in case of a nuclear accident in Akkuyu Nuclear Power Plant. (September 2021) - Tsabaris, Christos; Tsiaras, Konstantinos; Eleftheriou, Georgios; Triantafyllou, Georgios
Abstract: A 3-D hydrodynamic model, coupled with a Lagrangian drift model, was applied to simulate the dispersion of derived 137 Cs activity concentration in case of a nuclear accident in Akkuyu Nuclear Power Plant (NPP) located at the East Mediterranean Sea. The simulated near surface circulation presented a good skill in reproducing observed patterns from satellite altimetry data and existing literature. The dispersion pattern of dissolved 137 Cs was investigated on an annual and seasonal basis. In all seasons the dominant pathway of released 137 Cs had a westward direction, following the prevailing currents. The different dispersal patterns are mainly related to the intensity of the Asia Minor Current and the local circulation in the vicinity of the Akkuyu NPP. 137 Cs was transported during the first month to the neighboring coasts of the NPP, while after the fourth month the distribution of the plume was extended in areas of the Eastern Aegean Sea (including East Crete and Rhodes Islands), as well as at the Antalya coastline. After the 3rd month, the plume reaches areas in the Eastern Aegean Sea (including the Crete Island and Cyclades plateau) while after the 6th month it is spread gradually to the Ionian Sea and Levantine basin. At the end of the annual simulation, the plume appears significantly diluted, with relatively high concentrations found still in Dodecanese Islands and along the Aegean Turkish coast. The 137 Cs activity concentration starts to decline after the 9th month in most of the studied areas at the East Mediterranean Sea. The particulate 137 Cs was diminished within a month from the accident, due to sinking and its fast transformation to dissolved, showing a similar westward dispersion pattern.